Sintesis Senyawa C-2,8,14,20-TETRA-(2,4,5-Trimetoksi)Fenil Kaliks[4] Resorsinarena dari Senyawa 2,4,5-Trimetoksi Benzaldehida - Yoktan E Buraen; Pius D Ola; Reinner I Lerrick (Saintek Lahan Kering, 2019)
The synthesis of C-2,8,14,20-tetra-(2,4,5-trimethoxy)phenyl calix[4] resorcinarene from 2,4,5-trimethoxy benzaldehyde has been done. Through isolation of asaron from Timor Genoak (Acorus calamus) followed by its oxidation with K2Cr2O7, the C-2,8,14,20-tetra-(2,4,5-trimethoxy)phenyl calix[4] resorcinarene has, therefore, been accessed over reflux. The asaron has been isolated as 3.05% of yellow oil whilst, the oxidation produced 2,4,5-trimethoxy benzaldehyde with the yield of 49.49%. The C-2,8,14,20-tetra-(2,4,5-trimethoxy) phenyl calix[4]resorcinarene has been yielded as 89.29% of a brown solid.